2022-VA-979-ESGO Total excision of infrarenal vena cava in a patient with recurrent endometrial cancer. (20th October 2022) - Vatansever, Dogan; Donmez, Emin Erhan; Giray, Burak; Akçevin, Atif; Arvas, Macit; Taskiran, Cagatay
Abstract : Introduction/Background: Endometrial cancer is one of the common malignant tumors of the female reproductive system. The recurrence and 5-year overall survival rates of patients with FIGO I-II are 2–15 and 74–91%, respectively. Secondary cytoreductive surgery is associated with improved overall survival in patients with recurrent disease. This video aims to present metastasectomy along with the infrarenal vena cava in a patient with recurrent ovarian cancer. Methodology: A 68-year-old woman was admitted with a gross abdominal mass. She has been diagnosed with stage 1, grade 1 endometrial cancer, and underwent a primary staging surgery 2 years ago. The magnetic resonance imaging revealed a 43x39x49 mm abdominal mass involving vena cava inferior. Also, positron emission tomography scan showed a 45x47x50 mm metastatic lymph node extending to the aortocaval prevertebral area. Metastasectomy along with the infrarenal vena cava, resection of bulky paraaortic lymph nodes, partial resection of the duodenum, and duodenojejunostomy were performed as part of maximal secondary cytoreduction. Results: She stayed at the intensive care unit for one day and discharged without any grade 3 or 4 adverse event in post-operative period. Conclusion: Secondary cytoreduction for endometrial cancer with no residual disease is a major impact on survival, and maximal cytoreduction is necessary in selected cases. The management of this condition should be performed with expert multidisciplinary teams in gynecological oncology.